Implementasi Program Pemberdayaan Ekonomi Pada BAZNAS Kabupaten Jombang Bagi Masyarakat Kecamatan Bandarkedungmulyo - Umatin, Biba; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2021)
The government in economy has an important role to strengthen the process of society for full the basic needs and improving the quality of life. One of the government’s efforts in realizing society empowerment is form an institution called Badan Amil Zakat Nasional (BAZNAS). However, in its realization the program from BAZNAS has not fully succeeded in achieving the goals. This study aimed to discover the right evaluation for economic empowerment program from BAZNAS Kabupaten Jombang. This research is a descriptive qualitative. Data was collected through interviews, observation, and documentation. And the data analysis used the triangulation method of sources and the triangulation of technique. The result indicated that the mechanism for economic empowerment program in Kecamatan Bandarkedungmulyo from BAZNAS Kabupaten Jombang implements four stage process and there are several problems that can be evaluated to improve the program performance.